탄화수소 항공유의 열분해 반응에서의 연료 전환율 및 수소 생성률 정량분석 기법 연구 - 박승묵; Seung Mook Park; 강준수; Jun Su Kang; 이승현; Seung Hyeon Lee; 이형주; Hyung Ju Lee (한국분무공학회지, 2025)
Hydrocarbon aviation fuels are utilized as both coolant in regenerative cooling systems and propellant in a scramjet engine for hypersonic cruise vehicles. As the fuel absorbs a large amount of heat from high-temperature structures, it undergoes endothermic decomposition, producing hydrogen and low molecular-weight hydrocarbons. The fuel decomposed in this way significantly impacts both the cooling characteristics of the hypersonic vehicle and the combustion performance of the scramjet engine. Therefore, it is essential to analyze precisely the thermal decomposition characteristics of the fuel. In this study, quantitative methods based on gas chromatography (GC) analysis were established to evaluate the fuel conversion and hydrogen yield during the pyrolysis of hydrocarbon aviation fuel. Specifically, three applicable methods were proposed for measuring the fuel conversion, depending on the fuel composition and its pyrolysis characteristics. Furthermore, for the quantitative analysis of hydrogen, a novel method was introduced that calculates hydrogen yield by converting the hydrogen peak area using a calibration curve based on the hydrogen-to-methane ratio.